A novel cyclophilin gene from the dinoflagellate Prorocentrum minimum and its possible role in the environmental stress response. (November 2015) - Ponmani, Thangaraj; Guo, Ruoyu; Ki, Jang-Seu
Highlights: CYPs are well known for their housekeeping function, and potential oxidative stress defense. Participation of dinoflagellate CYP in stress defense and its structure were elucidated. Photosynthetic F v/ F m and PIABS indicated Cu 2+ and PCB affected dinoflagellate, and ROS production. Significant induction of CYP in dinoflagellates exposed to test pollutants SNP, copper, and PCB. Dinoflagellate CYP plays a cytoprotective role in oxidative stress response, and a novel biomarker. Abstract: Cyclophilins (CYPs) are a family of proteins that bind to cyclosporine and are thought to be involved in the stress response. In dinoflagellate algae, CYPs may function as a survival strategy in cells exposed to environmental stressors. Here, we identified a novel cyclophilin gene (referred to as PmCYP, comprising a 516-bp open reading frame, encoding a 171-aa protein with a molecular mass of 17.5 kDa) from the dinoflagellate Prorocentrum minimum, and evaluated the role of dinoflagellate CYP in cells exposed to environmental pollutants copper and polychlorinated biphenyl. In addition, we assessed the cytoprotective role of nitric oxide in relation to the expression of PmCYP . These stressors strongly affected the physiology of the cells, as judged by cell counting, reactive oxygen species (ROS) imaging, and photosynthetic parameters ( F v/ F m and PIABS ). PmCYP expression was significantly ( P  < 0.05) induced upon exposure of the cells to all the test pollutants used in this study. These clearly indicate that PmCYP plays a vital role in the oxidative stress response in dinoflagellate survival, although the gene was initially known only for its housekeeping function.